Sustainable smart photobioreactor for continuous cultivation of microalgae embedded with Internet of Things. (February 2022) - Tham, Pei En; Ng, Yan Jer; Vadivelu, Navintran; Lim, Hooi Ren; Khoo, Kuan Shiong; Chew, Kit Wayne; Show, Pau Loke
Graphical abstract: Highlights: Design, modelling and fabrication of continuous photobioreactor with extraction. Implementation of sensors into cultivation and extraction systems. Remote monitoring of sensors achieved with Blynk. High accuracy of the sensors was attained with low delay of remote monitoring. Abstract: This research work aims to fabricate an optimized up-scaled photobioreactor and extraction tank which incorporates the Internet of Things (IoT) for remote monitoring of selected parameters without being present in the lab as the industry is gradually moving towards the direction of remote operation. Several design factors were considered where modelling using ANSYS was carried out before the finalised design is drawn using AutoCAD. To monitor critical parameters that include liquid level, temperature, and pH condition during the operation of the tanks, water-proof sensors are implemented with the aid of Arduino NodeMCU board and the sensors are linked with Blynk, a smartphone application that allows remote monitoring via Wi-Fi connection. The sensors' results obtained using the Blynk application show high accuracy as compared with manual data except for photobioreactor liquid level. This shows that IoT and remote monitoring can be integrated successfully.